2019
DOI: 10.3390/ma12182873
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Models for the Prediction of the Hot Deformation Behavior of the 10%Cr Steel Alloy

Abstract: The aim of this paper is to establish a reliable model that provides the best fit to the specific behavior of the flow stresses of the 10%Cr steel alloy at the time of hot deformation. Modified Johnson–Cook and strain-compensated Arrhenius-type (phenomenological models), in addition to two Artificial Neural Network (ANN) models were established with the view toward investigating their stress prediction performances. The ANN models were trained using Scaled Conjugate Gradient (SCG) and Levenberg–Marquardt (LM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…When the materials constant can be evaluated based on Equation (14), the flow stress can be predicted from Equation (15) [ 14 , 32 ], which is derived from Equations (1), (2) and (5). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the materials constant can be evaluated based on Equation (14), the flow stress can be predicted from Equation (15) [ 14 , 32 ], which is derived from Equations (1), (2) and (5). …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the average root mean square error (RMSE) is a statistical measure for model performance evaluation [ 14 , 38 ], which is used to compare the four constitutive equations further. The expression of RMSE is as follows: where RMSE is the average root mean square error, E i is the experimental data and P i is the predicted value obtained from the model, and N is the total number of data employed in the investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of the above studies have identified that the strain-compensated Arrhenius-type equation has higher prediction accuracy. Therefore, the strain-compensated Arrhenius-type equation with a higher prediction accuracy is widely used to predict the flow stress of metals and alloys [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive modelling has been widely used to study metal flow behaviour taking into account the effects of process parameters [4,5]. The constitutive equations provide the intrinsic workability behaviour of the material during deformation [6]. The stress-strain state during deformation is complex [2], due to inhomogeneities effects of process parameters [4].…”
Section: Introductionmentioning
confidence: 99%